MINAT PESERTA DIDIK SMP NEGERI 13 PADA KEGIATAN EKSTRAKURIKULER SEPAK BOLA DI PONTIANAK - Fransiskus Karmianto; Ahmad Atiq; Andika Triansyah (Universitas Tanjungpura, 2021)
AbstractJunior high school at SMP 13 Pontianak is a school that has many extracurricular activities including football, but in the history of the journey from year to year there has never been any progress, but what is certain needs to be examined how the interests of students. The research method used in this study is a quantitative method with the form of survey research, the population in this study using purposive sampling. The results of the research that need to be conveyed. The interest of students at SMPN 13 Pontianak belongs to four categories, namely very good at 20%, good at 55%, enough at 24%, and less at 1%. Meanwhile, there is no or 0% lack of category. , The joy of students at SMPN 13 Pontianak belongs to 3 categories, namely very good at 50.5%, good at 40.2% and quite 9.3%. Whereas for the category of less and less at 0%. The persistence of students at SMPN 13 Pontianak was classified into 4 categories, namely very good at 9.3%, good at 55.7%, enough at 32%. The less category is 3% and the less category is 0%.Keywords ; Football Extracurricular, Student Interests.